Microwave Spin Control of a Tin-Vacancy Qubit in Diamond - Eric I. Rosenthal; Christopher P. Anderson; Hannah C. Kleidermacher; Abigail J. Stein; Hope Lee; Jakob Grzesik; Giovanni Scuri; Alison E. Rugar; Daniel Riedel; Shahriar Aghaeimeibodi; Geun Ho Ahn; Kasper Van Gasse; et al. (Physical Review X, 2023)
The negatively charged tin-vacancy (SnV^{-}) center in diamond is a promising solid-state qubit for applications in quantum networking due to its high quantum efficiency, strong zero phonon emission, and reduced sensitivity to electrical noise. The SnV^{-} has a large spin-orbit coupling, which allows for long spin lifetimes at elevated temperatures, but unfortunately suppresses the magnetic dipole transitions desired for quantum control. Here, by use of a naturally strained center, we overcome this limitation and achieve high-fidelity microwave spin control. We demonstrate a π-pulse fidelity of up to 99.51±0.03% and a Hahn-echo coherence time of T_{2}^{echo}=170.0±2.8  μs, both the highest yet reported for SnV^{-} platform. This performance comes without compromise to optical stability, and is demonstrated at 1.7 K where ample cooling power is available to mitigate drive-induced heating. These results pave the way for SnV^{-} spins to be used as a building block for future quantum technologies.